(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
This article presents a hygienic and epidemiological analysis of the incidence of liver diseases among populations living in areas contaminated with industrial waste. The study highlights the negative impact of environmental anthropogenic pollution—particularly heavy metals (lead, mercury, cadmium), organic compounds, and harmful substances in air and water—on liver health. Furthermore, the article analyzes international epidemiological studies and national public health data, elucidating the mechanisms by which industrial waste contributes to the development of hepatic pathologies.